Nephroprotective Activity of Dibenzo-α-Pyrone Derivatives in Gentamicin-Induced Nephrotoxicity and Oxidative Stress in Rats - Sawhney, Shalini K.; Singh, Monika; Puri, Dinesh; Hazarika, Sangeeta; Mishra, Achal (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives: The current work was done to determine the curative and nephroprotective activities of the synthesized butylamine derivative of Dibenzo-α-Pyrone (DAP). Materials and Methods: The synthesised drug at a concentration of 10, 20, and 40 mg/kg p.o. was given as a single dose in Albino rats with Gentamicin-induced nephrotoxicity. The changes in body weight of animals, if any, were monitored. Biochemical markers like serum creatinine, blood urea, and BUN concentrations were investigated to detect nephrotoxicity. In the tissues of the kidney, Glutathione (GSH) and lipid peroxidation (MDA) were also assessed. Results: 40 mg/kg p.o. of synthesised butylamine derivative of Dibenzo-α-Pyrone (DAP) exhibited significant (p<0.001) nephroprotective activity in the experimental animals. The reduced body weight and augmented biochemical markers (blood urea, serum creatinine, BUN levels), which were the attributes of gentamicin administration, were altered by the test sample. An increase in GSH and a decrease in Malondialdehyde (MDA) production also proved the nephroprotective activity of the synthesized sample. Conclusion: The derivatives of Dibenzo-α-Pyrone (DAP) demonstrated nephroprotective activity in vivo. This study based on experimental evidence suggests the probable mechanism of nephroprotection of the test sample might be due to its antioxidant property.
Keywords: Dibenzo-α-pyrone; Gentamicin; Nephrotoxicity; Urea; Creatinine; Glutathione; Lipid; peroxidation